PENGARUH AMBIGUITAS PERAN, KONFLIK PERAN, DAN KELEBIHAN PERAN TERHADAP INDEPENDENSI AUDITOR INTERNAL PEMERINTAH DAERAH (STUDI PADA INSPEKTORAT KOTA TOMOHON DAN KABUPATEN MINAHASA) - Pangkey, Grill G. U.; Kalangi, Lintje; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2023)
This study aims to examine the extent to which the role ambiguity kamislot, role conflict, and role overload affect the independence of local government internal auditors. The problem in this study, namely the indication of a lack of independence in the internal auditor of local government seen from the audit results are not detected by the inspectorate, but found by the external auditor of the audit board (The Audit Board of The Republic of Indonesia). The population of this study were all local government internal auditors in Tomohon city and Minahasa regency totaling 60 people. Samples in this study using sampling techniques from Isaac and Michael (1983) with an error rate of 1% and then determined 55 people as samples taken from the internal auditor Inspectorate of Tomohon city and Minahasa regency. The variables in this study are independent variables, namely role ambiguity (X1), role conflict (X2), and role overload (X3), while the dependent variable is the independence of local government internal auditors. The data of this study were taken from questionnaires distributed to respondents. The results of this study indicate that the ambiguity of the role has a significant negative effect on the independence of local government internal auditors, the role conflict does not have a significant effect on the independence of local government internal auditors, the overload of the role has a significant negative effect on the independence of local government internal auditors, as well as district.